Kejahatan Perdagangan Orang Dalam Perspektif Kejahatan Lintas Negara - Firda Rachma Aryani; Andi Aina Ilmih (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Regulations regarding cases of cross-border human trafficking in Indonesia have long existed and were confirmed with the ratification of the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) in 1979. Based on Law Number 7 of 1984 concerning Ratification of the Convention on the Elimination of All Forms of Discrimination against Women. This was then strengthened by the passing of Law no. On the 21st of 2007, legislation was passed to eradicate the crime of human trafficking. Compliance with the Palermo Protocol and the implementation of Law Number 21 of 2007 concerning the Eradication of the Crime of Human Trafficking is expected to increase legal protection for victims of transnational human trafficking, especially women.